2018
DOI: 10.1038/s41380-018-0102-9
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin modulates ventral tegmental area dopamine neuron activity and anxiety-related behavior through AdipoR1

Abstract: Adiponectin, a metabolic hormone secreted by adipocytes, can cross the blood-brain barrier to act on neurons in different brain regions, including those involved in stress-related disorders. Here we show that dopamine neurons in the ventral tegmental area (VTA) express adiponectin receptor 1 (AdipoR1). Intra-VTA infusion of adiponectin or the adiponectin mimetic AdipoRon in wild-type mice decreases basal dopamine neuron population activity and firing rate and reverses the restraint stress-induced increase in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 49 publications
3
52
0
Order By: Relevance
“…We have previously shown that adiponectin haploinsufficiency causes depression-and anxiety-related behaviors in mice via a central mechanism of action [21,24]. The present study provides evidence of 5-HT neurons as a neuronal substrate mediating the effects of adiponectin/ AdipoR1 signaling on depression-but not anxiety-related behaviors.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…We have previously shown that adiponectin haploinsufficiency causes depression-and anxiety-related behaviors in mice via a central mechanism of action [21,24]. The present study provides evidence of 5-HT neurons as a neuronal substrate mediating the effects of adiponectin/ AdipoR1 signaling on depression-but not anxiety-related behaviors.…”
Section: Discussionsupporting
confidence: 61%
“…Radioactive in situ hybridization for detecting AdipoR1 and AdipoR2 gene expression patterns were performed as previously described [21,24]. Briefly, the brain tissue (fresh frozen) was cut at a thickness of 20 μm, mounted onto polylysine coated slides and sequentially fixed in 4% paraformaldehyde for 1 h followed by a rinse in 2× saline sodium citrate (SSC) buffer (300 mM NaCl, 30 mM Na citrate, pH 7.2), acetylated in 0.1 M triethanolamine (pH 8.0) with 0.25% (vol/vol) acetic anhydride for 10 min and dehydrated through a graded series of alcohol (50-100%).…”
Section: In Situ Hybridizationmentioning
confidence: 99%
See 2 more Smart Citations
“…AdipoRON effectively improved insulin sensitivity and restored glucose homeostasis via the activation of AdipoR1-AMPK-PGC1α and AdipoR2-PPARα signaling pathways (162). AdipoRON treatment also mimicked adiponectin's established anti-diabetic effects (163) and ability to enhance cellular capacity for mitigating oxidative-stress (162,164), enhancing lipid/glucose oxidation in mitochondria (162,164), anti-inflammatory responses (162,(164)(165)(166)(167), lifeprolonging effect (162,163), anti-cancer effects (168,169), procell survival and anti-apoptotic effect (170,171), neuronal- (172,173), reno- (174,175), and cardio-/vascular-protective effects (165,(176)(177)(178)(179). However, exciting AdipoRON research in animal models has not been translated to establishment of a drug for human use and the search continues for additional small molecule AdipoR agonists which have little or no toxicity.…”
Section: Adiporonmentioning
confidence: 99%